Ruralização do ensino as ideias em movimento e o movimento das ideias (1930-1950) - Moraes, Agnes Iara Domingos (Editora Oficina Universitária, 2022)
"The book examines crucial issues for understanding schooling in rural areas and invites the reader to delve into the meanders of the inexorable historical flow of the movement of ideas. Who were the education ruralists? What actions did they take to make the movement stronger? What are the interests underlying the pedagogical proposals of a ruralized primary school and specific teacher training in rural normal schools? What is the presupposed intentionality in defending the fixation of workers in the countryside?" "It is, as the title suggests, "ideas in motion and [the] movement of ideas". But it's worth the warning. At no time does the author deal with these propositions as mere abstractions. They are ideas embodied in subjects and social and educational practices. Ideas of a national nature, such as the numerous books written by Sud Mennucci in dialogue with other authors such as Alberto Torres and ruralists of various stripes. Multiple dialogues that extend to the most varied corners of the country and crossed borders. Following the trails of missives received by Sud Mennucci from abroad, the present work gains special emphasis on the international circulation of the ideas of the Movement for the Ruralization of Teaching confronted with other political and institutional actions related to rural education." Excerpts from the Preface written by Prof. Dr. Rosa Fátima de Souza Chaloba "Campinas, June 2021. A sad end of autumn, devastated by the humanitarian tragedy of more than 473,000 deaths from Covid-19 in Brazil."